Effects of Caffeine Consumption on Autologous Full-Thickness Skin Graft Healing in an Animal Model - Tommy Supit; Neni Susilaningsih; Awal Prasetyo (Indian Journal of Plastic Surgery)
Background There exists contradictory evidence that states both the beneficial and deleterious effects of caffeine on wound healing. The general population might unknowingly consume caffeine that negatively affects wound healing. The main objective of this study is to investigate the effect of daily caffeine consumption on wound healing, specifically full-thickness skin graft (FTSG). Methods Forty Sprague–Dawley rats were randomized into four groups of equal size: control-dose (CD), low-dose (LD), medium-dose (MD), and high-dose (HD) caffeine groups. After autologous FTSG, all subjects in the intervention group were given daily pure caffeine gavage. The FTSG was explanted 7 days posttransplant. The graft viability, secondary contraction, and adherence were evaluated macroscopically, while fibroblast and collagen deposition was analyzed microscopically with hematoxylin eosin stain. Results The least graft viability (72.8 ± 20.7%, clinical wound assessment scale [CWAS] 2.4), highest secondary contraction (11.4 ± 10.5%), and fibroblast count (331.8 ± 88.6 cells/5 high power fields) were observed in the MD group. More collagen synthesis was observed in subjects who consumed caffeine. The level of secondary contraction, fibroblast count as well as graft viability and collagen synthesis were positively correlated. Conclusions Daily consumption of caffeine impairs graft viability when given in medium dose and increases collagen synthesis, irrespective of dosage. This study was in experimental rats; the results are not directly translatable to humans.